Effect of perceptual training without feedback on bilingual speech perception: Evidence from approximant-stop discrimination in L1 Spanish and L1 English late bilinguals - Black, Martha R.; Rato, Anabela; Rafat, Yasaman (Journal of Monolingual and Bilingual Speech, 2024)
This study examines the effect of perceptual training without feedback on the discrimination of the Spanish stop-approximant contrasts [b]–[B], [d]–[ð], and [g]–[y]. Of interest is if the aural repetition of target stimuli improves discrimination accuracy, how many repetitions are needed to observe a significant increase in perceptual discrimination accuracy, and if there is an effect of contrast type. Perception of the Spanish target phones was assessed in adult native (L1) Spanish speakers (n = 10) and L1 English bilingual learners of L2 Spanish (n = 23) via VCV nonwords over six blocks of 10 trials, featuring Spanish approximants and voiced stops in an AX discrimination task. Results indicate a significant effect of aural stimulus repetition on discrimination accuracy scores improvement. Significant improvements were observed for all three contrasts, with discrimination gradually improving across blocks. The data indicated that the [y]–[g] contrast was the most difficult contrast and exhibited the highest rate of discrimination accuracy improvement. Discrimination accuracy score improvements were also significantly larger for L1 English listeners in comparison with the L1 Spanish listeners for this contrast.